The Role of Reward Programs in Increasing Teacher Motivation at the Rumah Belajar Tutoring Institution - Wahyuni, Sri; Rahmawati, Siti Sofiah; Bachtillah, Andriansyah; Utami, Wanda Yulia; Neng Ayu Sri wahyuni (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This study aims to explore the role of reward programs in increasing the motivation of tutoring teachers at Rumah Belajar. Using a qualitative method with a case study approach, data was collected through in-depth interviews with tutoring teachers involved in the reward program and literature review. The results show that the reward program plays a significant role in increasing teacher motivation, both intrinsically and extrinsically. Teachers feel appreciated for their contributions, which encourages improved performance and commitment to the teaching process. Additionally, the reward program creates a more collaborative and healthy competitive work environment. This research aligns with motivation theory, which states that recognition and appreciation can strengthen individual motivation. This study provides practical implications for the management of Rumah Belajar in designing more effective reward programs to motivate teachers.